2020
DOI: 10.3390/jcm9123970
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Prophylaxis and Thrombotic Risk Stratification in the Varicose Veins Surgery—Prospective Observational Study

Abstract: Background: An invasive phlebological treatment is still not free from complications such as thrombosis. As in other surgical populations, not only the treatment modality, but also patient condition-related venous thromboembolism (VTE) risk factors matter. The current protocols used in varicose vein surgery centers are based mostly on individual risk assessment as well as on an implementation and extrapolation of general surgery VTE prophylaxis guidelines. In the presented study, the efficacy of routine VTE ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…In the field of vascular surgery were identified three studies that enrolled 2109 patients with varicose veins after endothermal ablation or stripping (n = 660), 50,51 and with arterial diseases, after open or endovascular reconstructions (n = 1449) 52 (Table S11, Supplemental Digital Content 1, http://links.lww.com/SLA/ E469). The CRS ranged from 2 to 8, and VTE events were reported in 3.4% to 4.0% of patients, including 4.0% of endothermal heat-induced thrombosis.…”
Section: Vascular Surgerymentioning
confidence: 99%
“…In the field of vascular surgery were identified three studies that enrolled 2109 patients with varicose veins after endothermal ablation or stripping (n = 660), 50,51 and with arterial diseases, after open or endovascular reconstructions (n = 1449) 52 (Table S11, Supplemental Digital Content 1, http://links.lww.com/SLA/ E469). The CRS ranged from 2 to 8, and VTE events were reported in 3.4% to 4.0% of patients, including 4.0% of endothermal heat-induced thrombosis.…”
Section: Vascular Surgerymentioning
confidence: 99%
“…Overall, to choose the proper prophylactic method and its duration, an adequate individual risk-stratification assessment is advocated: a recent prospective observational study addressed this issue and showed that both the Caprini score and venous clinical severity score questionnaire may be useful tools to stratify the risk of post-operative deep venous thrombosis (DVT) [ 12 ].…”
Section: Phlebologymentioning
confidence: 99%
“…На відміну від наявних ретроспективних звітів, у проспективних обсерваційних дослідженнях, коли всім хворим з ВХНК у післяопераційному періоді рутинно виконували сонографічне дослідження, було задокументовано набагато вищий рівень тромбозу глибоких вен. Так у групі з 377 пацієнтів, яким проводили видалення підшкірних вен та флебектомію, у 5,3 % діагностовано тромбоз глибоких вен [12].…”
Section: результати дослідженняunclassified